Pengaruh Penggunaan Limbah Buah Nanas (Ananas comosus L.Merr)Fermentasi dalam Pakan terhadap Produktivitas Broiler - M Syahayani; I Panjaitan; D D Putri (PETERPAN (Jurnal Peternakan Terapan), 2020)
The availability of commercial feed raw materials is a limiting factor that causes the price of commercial feed for broilers to be expensive. Therefore it is necessary to use additional feed or alternative feed with good nutritional content, available throughout the year at a relatively affordable and acessible. Pineapple waste is an alternative feed that is cheap, easy to obtain and available all year round. The weakness of pineapple waste is that the crude fiber content is quite high, but with fermentation technology this problem can be overcome. The research analyze the effect of fermented pineapple (Ananas comosus L.Merr) waste in feed on broiler productivity. The research was conducted from November to December 2019 at the Lampung State Polytechnic cattle stable. The experiment was designed with two treatments. The first treatment (P0 = control) of commercial feed without TLBNF. Second treatment (P1) Commercial Feed 92% + 8% TLBNF. The treated feed was given at the beginning of the third week to the end of the fourth week. The data for each variable was tested by means of the T- test. Based on the results and discussion, it can be concluded that: The use of 8% fermented pineapple waste flour (TLBNF) in commercial feed does not affect feed consumption, body weight gain, feed conversion